The Populations of Macrobenthos Organisms in The Peat Soil in Rawapening Reservoir - Ruswahyuni Ruswahyuni; William Nata (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2010)
Rawapening a reservoir in Semarang district, which holds the potential fisheries resources. Water in Rawapening comes from eighteen rivers, and there is only one outflow, i.e. Tuntang river. Peat soil in Rawapening has a high organic matter content. In terms of ecology, the presence of organic material is able to enrich the aquatic environment. The waters which has high content of organic material needs more oxygen to dicompose, so that the waters contain less oxygen. This condition can be harmful to aquatic organisms, especially benthic animals that are not active or have a limited movement. A discriptive field research was conducted in July 2008. The objectives of this research was to determine the populations of macrobenthos organisms in the peat soil which has different organic matter content The results show that the structure of macrobenthos populaion found in of 4 classes, consisting of: Oligochaeta, Gastropoda, bivalves and larvae of Insects. Of these 4 classes, there are 10 genera composed of 5 genera Oligochaeta, 1 genus of Bivalves, 3 genera of Gastropods and 1 genus of Cironomid. Chi-Square statistical analysis, showed that there are differences in macrobenthos population in the peat soils with different organic matter content in the waters Rawapening. Key Words: Macrobenthos. Peat Soil, Rawapening